2010
DOI: 10.1097/01.aids.0000391023.03037.1f
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of isoniazid preventive therapy for people living with HIV worldwide: barriers and solutions

Abstract: AIDS 2010, 24 (suppl 5):S57-S65

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
98
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(103 citation statements)
references
References 40 publications
4
98
0
1
Order By: Relevance
“…IPT was safe and effective, with no additional adverse events or additional drug resistance observed during IPT. Barriers to providing IPT include lack of availability, provider concern about promoting resistance, lack of clarity about appropriate candidates, and viewing IPT as a low priority among competing healthcare needs 16, 17. The variability observed in this study related to TB symptom investigation and IPT provision highlight a need to reinforce clear, consistent policies to ensure TB symptoms are investigated, but that IPT is provided to patients when active TB is ruled out.…”
Section: Resultsmentioning
confidence: 99%
“…IPT was safe and effective, with no additional adverse events or additional drug resistance observed during IPT. Barriers to providing IPT include lack of availability, provider concern about promoting resistance, lack of clarity about appropriate candidates, and viewing IPT as a low priority among competing healthcare needs 16, 17. The variability observed in this study related to TB symptom investigation and IPT provision highlight a need to reinforce clear, consistent policies to ensure TB symptoms are investigated, but that IPT is provided to patients when active TB is ruled out.…”
Section: Resultsmentioning
confidence: 99%
“…In those that have, the coverage remains low. 26,27 Previous evidence of IPT efficacy from randomized trials was derived mostly from studies conducted before the ART era. 22,[28][29][30][31] Evidence for the added value of IPT in patients receiving ART was mostly from patients with CD4+ counts of less than 500 cells per cubic millimeter.…”
Section: Discussionmentioning
confidence: 99%
“…Meta-analyses of randomized controlled trials have shown that IPT reduces the risk of active TB by 33% in people living with HIV, irrespective of skin test result, and by up to 64% in those with a positive tuberculin skin test [20,21]. Despite the substantial amount of clinical research that showed the benefits of IPT among people living with HIV, several barriers and operational challenges have hampered its roll out [22].…”
Section: Key Areas Of Operational Researchmentioning
confidence: 99%